Role of genetic polymorphisms in residual ridge resorption of mandible – A scoping review - Swapna B. Venkatesh; Smitha Sammith Shetty (Japanese Dental Science Review)
Residual ridge (RR) refers to the clinical alveolar ridge that remains after the bone and soft tissues have healed following tooth extraction. This ridge undergoes resorption, which is most rapid during the first six months of post-extraction. Subsequently, bone resorption continues at a slower pace throughout life, leading to significant loss of jaw structure over time. This process is commonly known as residual ridge resorption (RRR). RRR is a major factor contributing to the loss of stability and retention, especially in mandibular complete dentures. Severe resorption of the maxillary and mandibular ridges can also lead to a sunken cheek appearance, poorly fitting and unstable dentures, and associated pain and discomfort. Though the etiology of residual ridge resorption remains unclear. It is believed that certain cytokines and individual genetic variations may influence the RRR process. Thus, reviewing the studies that discuss genetic association with the health and resorption of alveolar bone may give clear view on the etiology, help to define the risk and strategize preventive and personalized management of the disease. Hence, we undertook a scoping review to understand the potential genetic factors influencing the Residual ridge resorption (RRR). This review employed PRISMA-ScR extension protocols for scoping review. The results of the study provided significant association between genetic polymorphisms, especially of single gene nucleotide polymorphisms with mandibular residual ridge resorption. Hence understanding the genetic predisposition of patients can guide the clinicians in identifying patients at higher risk of RRR, enabling preventive measures, proactive intervention and careful designing of the prothesis.